STUDY THE ISOLATION RATE AND ANTIBIOTIC RESISTANCE OF ACINETOBACTER SPP IN THE INTENSIVE CARE DEPARTMENT THANH NHAN HOSPITAL (Vietnam Journal of Community Medicine, 2021)
Objectives: To describe the isolation rate and antibiotic status of Acinetobacter ssp hospital-acquired bacteria in the intensive care unit. Methods: 1434 patient samples isolated patient samples, cultured, performed antibiogram, described cross-section. Results: 109/331 strains of Acinetobacter spp were isolated (32.9%) and mainly from respiratory specimens, catheters (76.1% and 14.7%). Acinetobacter spp has a high degree of antibiotic resistance to most of the antibiotics Ceftazidime: 91.7%, Cefepime 91.7%, gentamycine 91.7%, Amikacin 83.3%, Imipenem and Meropenem 75%, still sensitive 100 % with antibiotics Polimycin B and Colistin.
Keywords: Acinetobacter spp, nosocomial infections, antibiotic resistance